Beyond Least Squares Assumptions: Quantile Regression Estimates of the Heterogeneity in Commercialization–The Case of Sunflower-Producing Households in North West Province, South Africa - Abafe, Ejovi Akpojevwe; Oduniyi, Oluwaseun Samuel; Tekana, Sibongile Sylvia (Frontiers in Sustainable Food Systems, 2022)
The seamless, strong positive relationship across numerous nations, years, livestock, and crops on the welfare effects of commercialization highlights its importance in achieving the United Nations food security goals. This article examines the drivers of commercialization and heterogeneities existing at household levels. Here, the benefit of using a quantile regression technique is compared with the ordinary least square estimate to examine the relationships between smallholder commercialization and predictors. Using 177 observations from a single district in North West Province, South Africa, this paper empirically investigates the auxiliary benefit of the quantile regression technique as a strategic policy instrument to assess determinants and variations of agricultural commercialization. The principal finding of this study indicates that the degree of sunflower commercialization differs significantly across households in the study area. In addition, sunflower commercialization, at mean, is uniquely associated with hectares cultivated for sunflower production, household head, and market outlet. However, the emphasis of the ordinary least square is whether variation counts on average. This supposition may inaccurately depict the response distribution. For this reason, bootstrap quantile regression (QR) was implemented to tackle this limitation. The results of the QR indicate that heterogeneity in sunflower commercialization cannot be disregarded for the case of household size, market outlet, hectares cultivated for sunflower production, education, access to information, and gender. In addition, the market outlet and farming system appear to maintain their significant impact, although with varying magnitudes across all quantiles. Finally, the findings indicate that those in policy space promoting smallholder commercialization should be cognizant of the heterogeneity and potential benefits of efficacious sunflower promotion in South Africa and other African nations.